Secret seven fireworks - Blyton, Enid (Knight Sevenoaks, 1992)
The 11th of the adventures with Enid Blyton's Secret Seven. Originally published in 1958, this edition has been updated for today's young readers. The Secret Seven are none too pleased when Jack's annoying sister Susie forms a rival club called the Tiresome Three.